Programas de Pós-Graduação em Ensino de Ciências: um olhar para a formação continuada - Souza, Talita Martins Oliveira de (Universidade Federal de São Carlos, 2025)
Teacher training in Brazil has advanced in recent years, driven by public policies such as REUNI, which expanded access to higher education. The increase in undergraduate degrees shows that more professionals are preparing for teaching. However, there are still challenges, such as the persistence of traditional methodologies and the need for constant updating of educators. Continuing education has emerged as an essential path to improving the quality of teaching, but it faces obstacles such as lack of recognition and resources. In Science Teaching, it is essential that teachers go beyond rigid approaches and promote critical thinking in students. Academic research, especially in the master's program, can be a powerful tool for transforming teaching practice. In view of this, this study mapped, through documentary research, the Federal Universities in Brazil that offer Postgraduate Programs in Science Teaching, analyzing whether the official documents of the Programs comply with the designation of continuing education. The results indicate that among the Programs that indicate lines of research on Teacher Education, few explicitly refer to the term Continuing Education. In this sense, advancing these discussions is urgent, especially in times of rapid change. Recognizing this need and making it explicit through research indicates a commitment to valuing teachers, providing improvements in Brazilian education.
Postgraduate Programs in Science Teaching: a look at continued training
Keywords: Formação continuada; Ensino de Ciências; Mestrado Acadêmico; Continuing training; Science Teaching; Academic Master's; CIENCIAS HUMANAS::EDUCACAO::CURRICULO